A novel device for safe exteriorization of haptic in scleral fixation intraocular lens surgery - Baskaran, Prabu (Indian J Ophthalmol, 2020)
The aim of this study was to describe a novel device that has been designed to facilitate anterior segment and novice surgeons to perform extraocular needle-guided haptic insertion technique (X-NIT) for scleral fixation intraocular lens surgery (SFIOL). We performed SFIOL surgery using X-NIT device in 21 eyes of 21 patients. The mean preoperative best-corrected visual acuity (BCVA) was 0.5 ± 0.2 logarithm of minimum angle of resolution (log MAR), which improved by one or more lines postoperatively in all eyes. There were no intraoperative complications. Postoperatively, we noted minimal corneal edema in one patient and dispersed vitreous hemorrhage in one patient. The sharpness and angulation of the needle and the haptic holding ability of silicone stopper were found to be satisfactory. The X-NIT device may potentially improve the safety of SFIOL procedures by minimizing intraocular maneuvers.